Faktor-Faktor yang Mempengaruhi Kinerja Tenaga Penjualan Kartu Kredit Bank Rakyat Indonesia di Surabaya - Markus Bolianto Aprilian Larantukan (Universitas Pendidikan Ganesha, 2022)
Abstract The purpose of this study is to analyze the factors that influence the increase in sales force performance. Testing the effect of the variables of sales force competence, quality of salesperson and customer relationships, control systems, sales experience on sales force performance at Bank Rakyat Indonesia in Surabaya. his research is a causal research, where the research design is in accordance with the research objectives. The sample of this research is salespeople at PT. Bank Rakyat Indonesia in Surabaya, totaling 218 people. The sampling technique used to produce a representative sample is purposive sampling with the criteria that the salesperson used as the sample has at least one year of experience. The main data of this research is primary data generated through a questionnaire. The findings of this study are that there is a positive influence of sales force competence on sales force performance, there is a positive influence of relationship quality on sales force performance, there is a positive influence of the control system on sales force performance, there is a positive influence from sales experience. on sales force performance. The results showed that salesforce work experience was the variable with the most substantial effect, followed by the quality of the relationship between salesforce and customers, sales competence, and finally, the control system.